The X-files - Bowman, Rob 19620-; Duchovny, David 1960-; Anderson, Gillian 1968-; Landau, Martin 1928- (20th Century Fox Home Entertainment, 1998)
When a terrorist bomb destroys a building in Dallas, Texas, FBI Agents Dox Mulfer and Dana Sculy are drawn into a dangerous conspiracy surpassing anything they've ever encountered. With the dubious assistance of a paranoid doctor, Mulder and Scully risk their careers and their lives to hunt down a deadly virus which may be extraterrestrial in origin - and could destroy all life on earth. Their pursuit of truth pits them against the mysterious Syndicate, powerful men who will stop at nothing to keep their secrets safe, leading the agents from a cave in Texas, to the halls of the FBI, and finally to a secret installation in Antartica which holds the greatest secret of all.